Palominos have 50th anniversary (Raton Range Raton, New Mexico, 1976)
Newspaper Article on the 50th Anniversary of Jesus and Josefa Palominos.
Master list item #: 73
File location is in the Raton File Cabinet
Keywords: Palominos, Jesus; Palominos, Josefa; Segotta, Louise; Palominos, Jesse; Vallejos, Carlos; Vallejos, Ben; Vallejos, Tony; Vallejos, David; Vallejos, Chris; St. Joseph's Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Springer, New Mexico; Santa Fe, New Mexico; Tularosa, New Mexico; Alamagordo, New Mexico; Carizozo, New Mexico; Albuquerque, New Mexico; Pueblo, Colorado; Colorado Springs, Colorado; Trinidad, Colorado; Denver, Colorado; Colfax, Iowa; Kansas City, Missouri